1997
DOI: 10.1111/j.1469-7793.1997.503bb.x
|View full text |Cite
|
Sign up to set email alerts
|

ATP is released from rabbit urinary bladder epithelial cells by hydrostatic pressure changes–possible sensory mechanism?

Abstract: 1. The responses of rabbit urinary bladder to hydrostatic pressure changes and to electrical stimulation have been investigated using both the Ussing chamber and a superfusion apparatus. These experiments enabled us to monitor changes in both ionic transport across the tissue and cellular ATP release from it. 2. The urinary bladder of the rabbit maintains an electrical potential difference across its wall as a result largely of active sodium transport from the urinary (mucosal) to the serosal surface. 3. Small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
478
1
8

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 587 publications
(509 citation statements)
references
References 20 publications
22
478
1
8
Order By: Relevance
“…The experiments were repeated Ն3 times, and representative results are shown. show increased ion transport (Lewis and de Moura, 1982;Wang et al, 2003b), apical membrane turnover (exocytosis and endocytosis; Lewis and de Moura, 1982;Truschel et al, 2002;Wang et al, 2003a), and release of various mediators and neurotransmitters including ATP and adenosine (Ferguson et al, 1997;Lewis and Lewis, 2006;Yu et al, 2006). We observed that increased membrane tension (i.e., stretch) and not pressure was likely responsible for stimulating these changes.…”
Section: Role Of Stretch In Promoting Changes In Umbrella Cell Functionmentioning
confidence: 70%
See 1 more Smart Citation
“…The experiments were repeated Ն3 times, and representative results are shown. show increased ion transport (Lewis and de Moura, 1982;Wang et al, 2003b), apical membrane turnover (exocytosis and endocytosis; Lewis and de Moura, 1982;Truschel et al, 2002;Wang et al, 2003a), and release of various mediators and neurotransmitters including ATP and adenosine (Ferguson et al, 1997;Lewis and Lewis, 2006;Yu et al, 2006). We observed that increased membrane tension (i.e., stretch) and not pressure was likely responsible for stimulating these changes.…”
Section: Role Of Stretch In Promoting Changes In Umbrella Cell Functionmentioning
confidence: 70%
“…In addition to stimulating apical exocytosis, mechanical stimuli also trigger increased endocytosis, which modulates the increase in apical surface area (Truschel et al, 2002); however, the relationship of the endocytic and exocytic events and the mechanisms by which they are initiated and coordinated is not known. Previous studies showed that the electrophysiological responses of the uroepithelium are dependent on the direction the tissue is bowed (Ferguson et al, 1997); however, the physiological significance of these differences and the role of the distinct surface domains of umbrella cells in mechanotransduction is yet to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…The basal ATP release from the rabbit bladder epithelium is altered by amiloride, a blocker of ENaC. 43 Intravesical instillation of amiloride reduces the frequency of reflex voiding during bladder filling in anesthetized rats, and stretch-evoked ATP release from bladder strips is largely diminished by amiloride. 42 These indicate that ENaC expressed in the bladder epithelium is implicated in the mechanosensory transduction by controlling stretch-evoked ATP release.…”
Section: The Degenerin/epithelial Na + Channel (Deg/enac) Familymentioning
confidence: 99%
“…Freisetzung von Tachykininen (Lecci and Maggi, 2001), NO (Moon, 2002) und ATP (Ferguson et al, 1997). Nun existieren Quervernetzungen zwischen Urothel und subepithelialem Bindegewebe: TRPV1 scheint eine Grundvoraussetzung für eine urotheliale ATP Freisetzung bei Blasendistension zu sein (Birder et al, 2002), und das Urothel erweist sich hierbei als Hauptquelle der ATP Feisetzung bei zunehmender Blasenfüllung (Kumar et al, 2004).…”
Section: Besondere Erkenntnisse Der Wirkung Des Bont An Der Harnblaseunclassified
“…Nun existieren Quervernetzungen zwischen Urothel und subepithelialem Bindegewebe: TRPV1 scheint eine Grundvoraussetzung für eine urotheliale ATP Freisetzung bei Blasendistension zu sein (Birder et al, 2002), und das Urothel erweist sich hierbei als Hauptquelle der ATP Feisetzung bei zunehmender Blasenfüllung (Kumar et al, 2004). Dieses ATP, im Urothel also freigesetzt, bindet an P2X3 Rezeptoren im subepithelialen Bindegewebe, wodurch die Signalaktivität zum Rückenmark ingang gesetzt wird (Burnstock, 2001;Ferguson et al, 1997). Doch das Urothel erweist sich zusätzlich als…”
Section: Besondere Erkenntnisse Der Wirkung Des Bont An Der Harnblaseunclassified